Prognostic Value of CEA, CA19-9, CA125, CA724, and CA242 in Serum and Ascites in Pseudomyxoma Peritonei - Liang, Lei; Fang, Jingyang; Han, Xuedi; Zhai, Xichao; Song, Yan; Lu, Yiyan; Zhang, Qian; Ma, Ruiqing (Frontiers in Oncology, 2021)
Purpose: To investigate the expression of carcinoembryonic antigen (CEA), cancer antigen 125 (CA125), CA19-9, CA724 and CA242 in serum and ascites of pseudomyxoma peritonei (PMP) patients, and evaluate predictive value of these elevated biomarkers in pathological grade, CC and survival. Methods: From May 2009 to October 2019, a total of 512 patients diagnosed with PMP through pathology in Aerospace Center Hospital were enrolled. The serum and ascites tumor biomarkers were obtained. The diagnostic values between serum and ascites biomarkers in pathology and CC were compared by the receiver operating characteristic (ROC) curves. The correlation between pathology, cytoreduction and biomarkers was calculated by univariate and multivariate logistic regression. The associations between different number of elevated biomarkers and survival status were examined using univariate and multivariate backwards Cox proportional hazard regression models. Results: The results showed that the area under the ROC curves (AUROCs) in the diagnosis of CC were 0.798 (95% CI: 0.760-0.836) and 0.632 (95% CI: 0.588-0.676) in serum and ascites biomarkers, respectively. The elevated serum and ascites biomarkers were independent risk factors both for pathology and completeness of cytoreduction (CC). The one-year, three-year and five-year survival rate were 89.07 %, 73.22 % and 66.94 %, respectively. Longer survival was observed in patients who had less than two elevated serum biomarkers compared with those with 2-3 and 4-5 elevated serum biomarkers (P < 0.001). Conclusion: CEA, CA125, CA19-9, CA724 and CA242 in serum and ascites can be used to judge the severity and predict the resectability. Furthermore, different number of elevated biomarkers can help determine the prognosis of PMP.